2010
DOI: 10.1007/s00520-010-1027-2
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative assessment of the supportive care and resource needs of patients undergoing craniotomy for benign brain tumours

Abstract: Patients' supportive care needs are temporally dependent on disease course and treatment, and modifiable by demographic and psychosocial factors. Findings of this study show that patients with benign tumours lacked but needed many supportive care resources currently available to cancer patients. Many of the potential solutions to this current gap in supportive care involve extending support resources already available for cancer patients to patients with benign brain tumours. We thus suggest recommendations to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…13 Rather, such outcome differences, particularly post-operatively, may be due to varying social support between these groups. For instance, Wong et al 20 recently identified gaps in supportive care among all patients after meningioma resection. They commented on the lack of a formal support system for patients with benign brain tumors and recommended construction of Internet-based support groups, face-to-face support groups, individual peer support, and extending counseling services for patients with cancer as a means of fostering practical support for such patients post-operatively.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…13 Rather, such outcome differences, particularly post-operatively, may be due to varying social support between these groups. For instance, Wong et al 20 recently identified gaps in supportive care among all patients after meningioma resection. They commented on the lack of a formal support system for patients with benign brain tumors and recommended construction of Internet-based support groups, face-to-face support groups, individual peer support, and extending counseling services for patients with cancer as a means of fostering practical support for such patients post-operatively.…”
Section: Discussionmentioning
confidence: 98%
“…Although the Wong et al report identified no racial disparities within their cohort, the sample included only 29 patients, of which a majority was Caucasian. 20 It is possible that these gaps in supportive care may have a larger impact on the African-American population and contribute to the racial disparities seen among patients with meningioma.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of the distress screening time point (preoperatively- postoperatively- during course of therapy) on the screening results remains unclear [ 17 , 18 , 19 ]. A preoperatively increased distress is observed due to the fear of surgical intervention or the risk of death, coma or neurological and physical deficits after surgery [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prospect of undergoing neurosurgery is known to give rise to feelings of threat (Wong et al. 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, Rozmovits et al. (2010) and Wong et al. (2010) showed that persons with different type of benign brain tumours had a strong need for formal support and improved preoperative and postoperative information.…”
Section: Introductionmentioning
confidence: 99%